Features of interpersonal interaction of patients with socially significant disease - T. Yu. Udalova; N. V. Bagisheva; A. V. Mordyk; A. V. Kondrya; M. V. Moiseeva; D. I. Mordyk; I. I. Magnushevskaya (Лечащий Врач)
40 patients with infiltrative pulmonary tuberculosis (ITL) undergoing treatment in a TB dispensary were examined. Patients with newly diagnosed ITL are moderately closed, secretive, but able to listen to the opinions of others. They are distinguished by their straightforwardness and ease of communication, it is easier to get in touch with them in an individual conversation. Most of them are disciplined and responsible people, which allows to achieve a high level of adherence to treatment, but this does not exclude the need for constant support and participation of the doctor. Knowledge and consideration of psychological characteristics of patients with ITL will allow to develop individual approaches to managing patients with the involvement of specialists of various profiles to reduce time and improve the quality of treatment.